2022
DOI: 10.1155/2022/3745135
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate Ameliorates Oxidative Stress-Induced Intestinal Epithelium Barrier Injury and Mitochondrial Damage through AMPK-Mitophagy Pathway

Abstract: Sodium butyrate has gained increasing attention for its vast beneficial effects. However, whether sodium butyrate could alleviate oxidative stress-induced intestinal dysfunction and mitochondrial damage of piglets and its underlying mechanism remains unclear. The present study used a hydrogen peroxide- (H2O2-) induced oxidative stress model to study whether sodium butyrate could alleviate oxidative stress, intestinal epithelium injury, and mitochondrial dysfunction of porcine intestinal epithelial cells (IPEC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 45 publications
(55 reference statements)
0
25
0
Order By: Relevance
“…Additionally, as we have depicted above, mitochondrial dysfunction in the brain is prone to result in neurodegeneration. According to certain reports, butyrate can regulate mitochondrial dysfunction and lessen oxidative stress [ 41 , 42 , 43 ]. Li et al reported that butyrate can reduce oxidative stress-induced intestinal epithelium barrier injury and mitochondrial damage through the AMPK-mitophagy pathway [ 42 ], suggesting a possible mechanism by which NaB could exert its neuroprotective effects via improved mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as we have depicted above, mitochondrial dysfunction in the brain is prone to result in neurodegeneration. According to certain reports, butyrate can regulate mitochondrial dysfunction and lessen oxidative stress [ 41 , 42 , 43 ]. Li et al reported that butyrate can reduce oxidative stress-induced intestinal epithelium barrier injury and mitochondrial damage through the AMPK-mitophagy pathway [ 42 ], suggesting a possible mechanism by which NaB could exert its neuroprotective effects via improved mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, butyrate activates nuclear transcription factors, such as peroxisome proliferator-activated receptor γ [ 67 ], to antagonize nuclear factor-κB signal transduction and exert an anti-inflammatory effect in the gut. It also activates the ATP-activated protein kinase signaling pathway to alleviate oxidative stress-induced intestinal epithelium barrier injury [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of autophagy in oxidative stress injury is still controversial. Autophagy has been reported to play a positive effect in promoting cell survival and antiapoptosis under H 2 O 2 -induced oxidative stress [40,41]. However, other studies have shown that H 2 O 2 induces cytotoxicity by triggering autophagy [42,43].…”
Section: Discussionmentioning
confidence: 99%